PREDIKSI PERINGKAT OBLIGASI: PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI PEFINDO TAHUN 2013 - 2017 - Rully Anandia Suprapto; nur Aini (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study aims to determine the effect of Profitability, Leverage, Liquidity, Company Size on bond ratings in non-financial companies registered at PT. PEFINDO from 2013-2017. The sample used in this study was 157 non-financial companies.The sampling method uses purposive sampling with the research period from 2013 to 2017. The relationships and / or influences between variables are explained using multiple linear regression analysis methods.This study consists of the results of the study showing that 1) Profitability does not bond ratings 2) Leverage bond ratings 3) Liquidity does not bond ratings 4) Company size bond ratings. Keywords: Bond Ranking, Profitability, Leverage, Liquidity, Company Size